A Research Synthesis of Therapeutic Interventions for Whiplash-Associated Disorder (WAD): Part 4 – Noninvasive Interventions for Chronic WAD - Robert W Teasell; J Andrew McClure; David Walton; Jason Pretty; Katherine Salter; Matthew Meyer; Keith Sequeira; Barry Death (Pain Research and Management)
Whiplash-associated disorder (WAD) represents a significant public health problem, resulting in substantial social and economic costs throughout the industrialized world. While many treatments have been advocated for patients with WAD, scientific evidence supporting their effectiveness is often lacking. A systematic review was conducted to evaluate the strength of evidence for various WAD therapies. Multiple databases (including Web of Science, EMBASE and PubMed) were searched to identify all studies published from January 1980 through March 2009 that evaluated the effectiveness of any clearly defined treatment for acute (less than two weeks), subacute (two to 12 weeks) or chronic (longer than 12 weeks) WAD. The present article, the fourth in a five-part series, evaluates the evidence for noninvasive interventions initiated during the chronic phase of WAD. Twenty-two studies that met the inclusion criteria were identified, 12 of which were randomized controlled trials with ‘good’ overall methodological quality (median Physiotherapy Evidence Database score of 6). For the treatment of chronic WAD, there is evidence to suggest that exercise programs are effective in relieving whiplash-related pain, at least over the short term. While the majority of a subset of nine studies supported the effectiveness of interdisciplinary interventions, the two randomized controlled trials provided conflicting results. Finally, there was limited evidence, consisting of one supportive case series each, that both manual joint manipulation and myofeedback training may provide some benefit. Based on the available research, exercise programs were the most effective noninvasive treatment for patients with chronic WAD, although many questions remain regarding the relative effectiveness of various exercise regimens.